Innovation and competitiveness: organizational culture and business model (2017)
This article has as its starting point a review of the literature on innovation and competitive advantage published in some of the most important Colombian Journals, given the strong relationship between these terms and the growing importance and interest that have been gaining in Latin American business and academia. As a search results and review of the state of art of the last 10 years, it can identify insights about the important role assigned to the Business Model (MN) and Organizational Culture (CO) concept. They stand out and are often identified as common elements in the implementation of innovation and development of competitive advantages in organizations that exposed to a dynamic of change seek to understand and adjust to pro-environment to ensure their permanence in the market.